The Influence of Digital Game-Based Learning on Student Vocabulary Enrichment (Baamboozle and Wordwall Implementation) - Destiawati Syaharani Rahayu; Iyan Irdiyansyah; Gusnadi (Asshika: Journal of English Language Teaching & Learning, 2024)
Baamboozle can be an effective learning medium for teaching vocabulary in vocational English classes. Learning English in vocational contexts, such as hospitality, requires engaging methods that suit students’ needs. This research aims to investigate whether there is a significant effect of using Baamboozle and Wordwall as digital game-based learning media, and whether there are significant differences between the two in enriching students’ vocabulary mastery on Front Office topics, especially Check-In service. The researcher used a quasi-experimental design with pre-test and post-test given to both experimental and control groups. The experimental group was treated with Baamboozle, while the control group used Wordwall. The results of the paired sample t-test showed a significant improvement in both groups. However, the independent t-test revealed a significant difference in favor of the experimental group, indicating that Baamboozle was more effective in enriching vocabulary. The combination of Baamboozle’s collaborative game-based features and role-play activities contributed to students’ better vocabulary comprehension and engagement. Based on the result, it is recommended that teachers consider using interactive digital games like Baamboozle to make vocabulary learning more effective, contextual, and enjoyable, especially in vocational schools where practical communication is essential.